The role of Psychological Contract and Abusive Supervision on Employee Turnover Intention: A Mediated-Moderation Model (KASBIT Business Journal, 2020)
The foucus of this research is to explore the relationship of psychological contract and abusive supervison with the turnover intention mediated by employee wellbeing and moderated by work life balance. This is a an original contribution to the existing literature. In order to identify the relationships among variables, 181 employees working in different bank have been taken a sample. The data was collected by self-administrative questionnaire. The structural equation modeling has been done with the help of Smart PLS. This research applied the theorectrical lens of conservation of resources (COR) theory. The findings were also consistent with prior studies concerning the interactive relationship between psychological contract, abusive supervision, employee wellbeing, work-life balance and their influence on turnover intention. The results of this study indicated that abusive supervision, work life balance and psychological contract breach are positively related with employee wellbeing while turnover intention has negative relation with employees’ wellbeing. Moreover, employers should avoid unrealistic promises to their work force and well behave them, they should also provide the wellbeing opportunity and help them in work life balance in order to avoid turnover intention
Keywords: Psychological Contract; Abusive Supervision; Employee Wellbeing; Work-Life Balance; Turnover Intention; Banking Sector